Sistem Informasi Geografis Penyebaran Alumni di STIMIKOM Stella Maris Sumba Berbasis Web - Mariani Ngongo; Cecilia Dai Payon Binti Gabriel; Katarina Yunia Riti (International Forum of Researchers and Lecturers, 2024)
WebGis is a service that has geographic information. Geographic information systems have many spatial data types, namely points, lines, areas, and surfaces. GIS is a computer-based application whose data will be managed by spatial and attribute data. The distribution of graduates on Sumba Island is very large and has not been properly recorded so the data collection has not been properly recorded. Therefore, researchers conduct research and find solutions by recording alumni and managing the data into a system that can be recorded properly through spatial data information in the form of maps with databases so that the search for alumni distribution can be tracked properly.